A study of the interaction between inverted cucurbit[7]uril and symmetric viologens. Issue 1 (5th January 2017) - Gao, Zhongzheng; Bai, Dong; Chen, Lixia; Tao, Zhu; Xiao, Xin; Prior, Timothy J.; Redshaw, Carl
Abstract : The interaction between iQ[7] and a series of symmetric viologen derivatives, namely dicationic dialkyl-4, 4′-bipyridinium guests where the alkyl is CH3 (CH2 ) n with n = 0 to 6, has been studied in aqueous solution and solid state. Abstract : The interaction between inverted cucuribit[7]uril (iQ[7]) and a series of symmetric viologen derivatives bearing aliphatic substituents of variable length, namely dicationic dialkyl-4, 4′-bipyridinium guests where the alkyl is CH3 (CH2 ) n with n = 0 to 6, has been studied in aqueous solution by 1 H NMR spectroscopy, electronic absorption spectroscopy, isothermal titration calorimetry and mass spectrometry. In the case of both n = 5 (HV 2+ ) and 6 (SV 2+ ), single crystal X-ray diffraction revealed the composition to be [(iQ[7])2 (HV)2 ][CdCl3 Br][H3 O + ]2 [H2 O]12.5 and (iQ[7])2 (C7-SV)1.5 [CdCl4 ]4 (H3 O + )5 (H2 O)8, respectively, with both adopting an externalB -type structure (the alkyl chains of the viologen reside within the iQ[7]).